On Fuzzy Improper Integral and Its Application for Fuzzy Partial Differential Equations - ElHassan ElJaoui; Said Melliani (International Journal of Differential Equations)
We establish some important results about improper fuzzy Riemann integrals; we prove some properties of fuzzy Laplace transforms, which we apply for solving some fuzzy linear partial differential equations of first order, under generalized Hukuhara differentiability.